2012
DOI: 10.1021/ie201873z
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Sorption by Metal Ion-Loaded Fibrous Protein

Abstract: A new metal ion-loaded (Zr(IV), Al(III), Fe(III)) fibrous protein (MFP) was synthesized and characterized by surface charge (pH pzc ), surface morphology, and infrared spectrum. The pH pzc (point of zero charge) of MFP was located in alkaline zone, higher than that of fibrous protein (FP, 5.5−6.0) before impregnation. FTIR studies indicated that metal hydroxyl functional groups (M−OH, M representing surface metal ions of Zr(IV), Al(III), Fe(III)) played an important role in fluoride adsorption by MFP. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In spectra of CrFP, the sharp peaks at1535 cm −1 and 1240 cm −1 belonged to CONH amide II and C N stretching of amide III, respectively [25], and the bands observed between 1466 and 1600 cm −1 were typical subtle structure of aminophenol, peak at 1081 cm −1 was attributed hydroxyl group of Cr(III) oxide [25,26]. For ACrFP, the wide peak around 3385-3428 cm −1 illustrated the appearance of amine groups [18], bands at 2946-2954 cm −1 were symmetric vibration of CH 2 , and the bands of 1647-1654 cm −1 were stretching vibration of COO, C O, C N (amide I) peptidic bond of proteins [25][26][27]. In addition, the new band at 1336 cm −1 representing C N stretching indicated the insertion of amine groups onto CrFP backbone, and new strong adsorption band in the region of 1040-1100 cm −1 corresponded to the COC group vibrations [28].…”
Section: Characterizationmentioning
confidence: 99%
“…In spectra of CrFP, the sharp peaks at1535 cm −1 and 1240 cm −1 belonged to CONH amide II and C N stretching of amide III, respectively [25], and the bands observed between 1466 and 1600 cm −1 were typical subtle structure of aminophenol, peak at 1081 cm −1 was attributed hydroxyl group of Cr(III) oxide [25,26]. For ACrFP, the wide peak around 3385-3428 cm −1 illustrated the appearance of amine groups [18], bands at 2946-2954 cm −1 were symmetric vibration of CH 2 , and the bands of 1647-1654 cm −1 were stretching vibration of COO, C O, C N (amide I) peptidic bond of proteins [25][26][27]. In addition, the new band at 1336 cm −1 representing C N stretching indicated the insertion of amine groups onto CrFP backbone, and new strong adsorption band in the region of 1040-1100 cm −1 corresponded to the COC group vibrations [28].…”
Section: Characterizationmentioning
confidence: 99%
“…The C-O-C stretching is also observed as an overtone at 616 cm -1 and the band at 1066 (C-O), 1031 (C-N) and 835 (C-N) cm -1 suggesting that chitosan is present in the polymeric composite[21,22]. The wide peaks in the region of 1513-1326 cm -1 and the high intensity band at 624 cm -1 region was attributed to the lanthanum bond[23].The results indicated that the La(III) ions have a greater interaction with the O-H of carboxylic groups to form La-DLE complex. After fluoride treatment (f-CS@La-IDAMP), the shifting of peaks to higher wavenumber confirms the presence of fluoride in the complex as shown in Fig.…”
mentioning
confidence: 92%
“…Several defluorination technologies, such as adsorption [ 9 , 10 ], ion exchange [ 11 , 12 ], precipitation [ 13 ], membrane separation [ 14 , 15 ], electrocoagulation flotation [ 16 ], and electrodialysis [ 17 ], have been developed and evaluated. Among these methods, adsorption is still the first option owing to its high removal rate, easy operation and cost-effectiveness [ 18 20 ]. However, developing a suitable adsorbent with acceptable adsorption capacity, high regeneration efficiency, and strong adaptability remains difficult [ 21 ].…”
Section: Introductionmentioning
confidence: 99%